Development of Project Based Learning Type Practicum Guide with Zoom Cloud Meeting on Electrolyte and Non-Electrolyte Materials in SMA - Zakiah, Zakiah; Maisura, Maisura (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research is a research development practicum guide in the field of chemistry education. The aims of this research are 1) to getpractical guide based on type syntax Project Based Learning 2) Get the type practicum guide Project Based Learning. 3) Significant increase in learning outcomes that are taught using Zoom Cloud Meetingand a practical guide developed with the type Project Based Learning. 4) The effectiveness of the learning process that is taught by using Zoom Cloud Meeting by usingtype practicum guide Project Based Learning. The stages in this research are (1) Syntax analysis of the Project Based Learning learning model to determine the components of the chemistry practicum guide according to the Project Based Learning type, (2) Compile and develop a chemistry practicum guide for electrolyte and non-electrolyte materials in accordance with the Project Based type syntax. Learning, (3) Standardization or or feasibility test of practicum guides to teacher validators, (4) Implementation of practicum guides for class X students of SMA Negeri Unggul Sigli, (5) Analyzing the effectiveness of Project Based Learning type practicum guides in electrolyte and non-electrolyte learning by using Zoom Cloud Meetingwhich has been tested. The results of the feasibility test for the Project Based Learning type practicum guide 3.50. While the effectiveness of the use of Project Based Learning type practicum guides seen from student learning outcomes, it is known that the experimental class I that does not use Project Based Learning type practicum guides usesZoom Cloud Meeting an average of 56.00 with an increase in learning outcomes of 51.4% while the experimental class II which uses a Project Based Learning type practicum guide by using Zoom Cloud Meetingan average of 81.75 with an increase in learning outcomes of 58.8%. So it can be concluded that the Project Based Learning type practicum guide is feasible to be used as a practicum guide in schools, with an increase in learning outcomes using a Project Based Learning type practicum guide that usesZoom Cloud Meeting higher value compared to student learning outcomes without using a practicum guide